Komunikasi Antar Budaya Motif Batik Cina - Agung Wicaksono (Ars: Jurnal Seni Rupa dan Desain, 2011)
Cross-cultural Communication in Batik Cina Motif.  Batik Cina is a motif that is created by the Chinese people or their descents living at the northern coastal area of Java. This motif plays a quite important role in batik development in Java. It contains cross-cultural communication patterns that are beneficial to reduce social tension. A dialogue by means of the exchange of cultural icons brings about a new style of batik motif called batik Cina. The motif is a combination of the China, Java, and Europe motif elements. It is a case of a mutual strengthening.Keywords: communication cross cultural, Batik Cina Motif